Routine diagnosis of large granular lymphocytic leukaemia by Southern blot and polymerase chain reaction analysis of clonal T cell receptor gene rearrangement. Issue 2 (April 1997) - Ryan, D K; Alexander, H D; Morris, T C
Abstract : AIMS: To compare the polymerase chain reaction (PCR) assay with standard Southern blot (SB) hybridisation for the detection of clonal T cell receptor (TCR) gene rearrangements in large granular lymphocyte (LGL) proliferations; to evaluate the reliability and practicality of the methods for routine diagnostic use; and to determine the sensitivity of the PCR method. METHODS: Blood lymphocytes were isolated from 12 patients with persistent CD3+CD8+ lymphocytosis with LGL morphology. Clonal rearrangements of the TCR gene were demonstrated by SB hybridisation with a TCR beta constant probe, and by PCR amplification of portions of the TCR beta and TCR gamma genes. RESULTS: Monoclonal TCR beta gene rearrangements were detected in eight patients (67%) by PCR analysis and five patients (42%) by SB hybridisation. PCR analysis also showed that seven patients (58%) had monoclonal TCR gamma gene rearrangements. All cases which had TCR beta clonal rearrangements shown by SB hybridisation were similarly identified by PCR. Sensitivity tests suggested that the TCR beta PCR technique was capable of detecting clonality in as little as 50 pg of DNA. The TCR beta primers could detect one clonal cell in approximately 200 or more normal cells (< 0.5%), a sensitivity level that at least doubles that of the SB hybridisation technique. CONCLUSIONS: The use of PCR technology proved to be superior to SB hybridisation for the routine investigation of suspected cases of LGL leukaemia. Nine patients (75%) in this study were found to have TCR beta and/or TCR gamma monoclonal gene rearrangements. This approach is ideal for distinguishing between reactive and clonal LGL proliferation in a routine diagnostic laboratory.